2013
DOI: 10.5430/jnep.v4n3p133
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate nursing students’ belongingness in clinical learning environments: Constructivist grounded theory

Abstract: Background: Experiential learning within clinical practice settings is a substantial component of undergraduate nursing education. This study described baccalaureate nursing students' perception of how their belongingness evolves in clinical learning environments through partnerships with their clinical educator and unit-based nurses. Methods: The design of this study was constructivist grounded theory. The setting was a single four year baccalaureate nursing program located in Ontario, Canada. Eighteen studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 28 publications
(28 reference statements)
0
28
0
Order By: Relevance
“…Satisfied connection was found to support students' learning (Schoonbeek and Henderson, 2011). Indeed, final year undergraduate nursing students in Kern et al (2014) study reported feeling a sense of belonging when they demonstrated competency while on clinical placement. Findings from the present study may have resulted from students not having enough time on their allocated clinical placement areas to develop this type of connection.…”
Section: Discussionmentioning
confidence: 78%
“…Satisfied connection was found to support students' learning (Schoonbeek and Henderson, 2011). Indeed, final year undergraduate nursing students in Kern et al (2014) study reported feeling a sense of belonging when they demonstrated competency while on clinical placement. Findings from the present study may have resulted from students not having enough time on their allocated clinical placement areas to develop this type of connection.…”
Section: Discussionmentioning
confidence: 78%
“…Of the 144 student responses, nearly 20% were primarily concerned about “not being welcome” on the unit and perhaps being the target of bullying (Levett-Jones et al, 2015). Similarly, Kern et al (2014) found in their qualitative research that nursing students felt unwanted by unit nurses which in turn prevented them from achieving a sense of belonging in the clinical setting. In another study of 2 nd and 3 rd year nursing students in Australia, researchers found students perceived a hierarchical environment where nursing students were treated poorly by the clinical nurse staff created a hostile learning environment (Curtis et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding these aspects may provide important information from which interventions can be developed. Beliefs about bullying encountered in the clinical setting include a view that bullying is unavoidable and something to be dealt with (Curtis, Bowen, & Reid, 2007) or occurs because students are “not wanted” or do not belong in the clinical unit (Thomas & Burk, 2009; Kern et al, 2014). Researchers indicated that nursing students respond to bullying by feeling disrespected, not valued, and powerless (Curtis et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is obvious that sense of belonging leads to enthusiastic concentration on learning for better comprehension as well as to high quality communication with staffs and perception of their supports (14). Students unable to secure belonging learn in clinical settings as outsiders, unfamiliar with the nursing environment (15).…”
Section: Introductionmentioning
confidence: 99%